Challenges faced by Teachers and Students towards Quality Assurance of Education amidst Covid-19 Pandemic: Tantangan Tenaga Pengajar dan Pelajar Terhadap Jaminan Mutu Pendidikan di Tengah Pandemi Covid-19 - Irwan Irwan; Rustan Santaria (Universitas Cokroaminoto Palopo, 2020)
Pandemic of Covid-19 influnces many things in real life. It also influences academic atmosphere and the culture of teaching and learning at schools. Government regulates “Study from Home” in order to prevent the spread of the virus. This study uses library research method in collecting data from various references. The objective of this study is to find out the challenges faced by the teachers and the learners in reaching the good quality of education amidst pandemic Covid-19. We found that the challenges faced by the teachers and learners are complicated. It cannot be separated from government’s role in assisting the governments’ regulation.